Thermoresponsive hydrogel maintains the mouse embryonic stem cell "naïve" pluripotency phenotype1. (15th October 2015) - Mangani, Christian; Lilienkampf, Annamaria; Roy, Marcia; de Sousa, Paul A.; Bradley, Mark
<x xml:space="preserve">Abstract</x> A chemically defined hydrogel HG21, which allows enzyme-free passaging, is a substitute for gelatin allowing standardised and inexpensive mESC culture.